Existence of solutions to quasilinear functional differential equations - Syed Abbas (Electronic Journal of Differential Equations, 2009)
In this article we use the theory of C0-semigroup of bounded linear operators to establish the existence and uniqueness of a classical solution to a quasilinear functional differential equation considered in a Banach space.